A internacionalização da educação superior na pós-graduação das universidades do sudoeste do Paraná (UNIOESTE/UTFPR/UFFS): qual (is) perspectiva(s)? - Hotz, Celso (2023)
This thesis was defended in the Education Graduate Program at the Western Paraná State University (Universidade Estadual do Oeste do Paraná), in Cascavel Campus, whose area of research concentration is Education, related to Education, Social Policies and State line. In the academic and social environment, there is a consensus that the best universities are the most internationalized ones, i.e., the so-called World Class Universities. However, what about those ones that are not part of this select group, especially the universities whose campus are in state’s interior? Thus, the objective of this thesis is to analyze the internationalization perspectives present at Doctoral Programs of public universities located in the Southwest of Paraná State, in Brazil, for the purpose of verifying what is/are the perspective(s) that guide the internationalization process, within doctoral and post-doctoral programs, and short courses attended by foreign professors. Furthermore, to carry out a survey of academic articles, attendance at international courses, professors’ Curriculum Lattes, and in the Quadrennial CAPES from 2008 to 2023. To this end, the following specific objectives were placed: a) To understand the concept of Internationalization of the Higher Education present in the hegemonic perspective of coloniality, the so-called World Class University; b) To understand the concept of Internationalization of the Higher Education from the perspective of decoloniality, which is still under construction; c) To analyze the purposes of internationalization at public universities in the Southwest of Paraná, as follows UNIOESTE, UTFPR and UFFS, in the graduate studies through the identification of the countries and institutions with which these universities have agreements with, and what actions are produced from these agreements within the doctoral, post-doctoral and short courses. Given the conditions of subordinate dependence and the position of Brazil in the international division of labor; however, at the same time, the necessity to meet regional development, the thesis defended here is that the Graduate Programs studied neither align with the hegemonic, colonial perspective of Internationalization of Higher Education, nor align with the non-hegemonic perspective, decolonial internationalization. To achieve the proposed objective, a bibliographic research was carried out, seeking the foundations of the research theme, as well as a data survey of three Doctoral Programs. Two main perspectives of Internationalization of Higher Education were analyzed. First, the hegemonic perspective, here described as coloniality. Second a non-hegemonic perspective, described as decoloniality. In conclusion of this study, although one of the three universities surveyed has in its internationalization policy the hegemonic perspective of the World Class University, none of the three universities evidenced the tendency towards this perspective. Moreover, in a dialectical and contradictory way, none of the three universities are linked to the non-hegemonic or decolonial perspective. Despite not aligning with either of the two perspectives of internationalization, I defend that the universities with campus located in the State’s interior can be considered "flagship universities", since they have a very high potential conditions to contribute to the social and economic development of the Southwest of Paraná, regardless of their classification in the international ranking.